The cerebellar-related cognitive function is sensitive to aging: implications for early detection - Ma, Qianying; Pu, Min; Li, Meijia; Liu, Ling; Wu, Ruilin (Frontiers in Aging Neuroscience, 2025)
BackgroundAccumulating evidence demonstrated that the cerebellum contributes to a wide range of sensorimotor and cognitive functions. However, the relationship between cerebellar function and cognitive abilities in normal aging populations remains unclear.MethodsThe present cross-sectional study tested cerebellar-related cognitive changes across middle to late adulthood using the Cerebellar Cognitive Affective Syndrome (CCAS) scale and a perceptual serial reaction time (SRT) task. Participants were divided into three groups: early-middle-aged adults (N = 18, 30–45 years), late-middle-aged adults (N = 19, 46–57 years), and older adults (N = 18, 60–78 years).ResultsAlthough all participants were identified as cognitively healthy by the Mini-Mental State Examination (MMSE), older adults showed significant impairments in the CCAS scale, especially in semantic and phonemic fluency, category switching, digit span backward as well as cube drawing/copy. In the perceptual SRT task, older adults responded slower than their counterparts, reflecting age-related impairments in sensorimotor integration efficiency. However, there were no age-related group differences in learning new procedural knowledge. Importantly, participants with poorer CCAS performance demonstrated slower response speed and lower accuracy in the perceptual SRT task.DiscussionThe current results indicate a dissociation between general cognitive scores screened by MMSE and cerebellar-specific cognitive impairments. Furthermore, as the cerebellum plays a critical role in both sensorimotor and cognitive domains, the current study highlight the importance of incorporating screening tools which are sensitive to cerebellar functions in aging research.